Economic regulation of air transport in the light of the changing legal environment (Ius Novum, 2022)
Liberalization of air transport services and changes in the external transportation policy ofthe EU caused that the economic regulation of the market is also changing. As a result, thestandards that are in force based on bilateral agreements and laying down restrictive attitudetowards access to the market of air transport are breached. The scope of regulations covered ininternational aviation agreements is also widened by the addition of issues that were subject tothose agreements to a limited extent if at all. The article analyses those changes and evaluatesthem from the perspective of the regulation of access to aviation services among variousstates’ economies.
Keywords: economic regulation of the market; air transport; liberalization; Chicago bilateral system; open skies agreements; Common Aviation Area agreements; freedoms of the air; cabotage; inter-regional regulation; freedom to provide services